척추 수술 후 영상 평가: 초기 및 중장기 합병증 - 박재휘; 김동현; 채지원; 김효진; 서지운; 손진영; Jae Hwi Park; Dong Hyun Kim; Jee Won Chai; Hyo Jin Kim; Jiwoon Seo; Jin Young Son (Journal of the Korean Society of Radiology, 2024)
As the number of spinal surgeries being performed expands, the number of medical imaging procedures such as radiography, CT, and MRI is also increasing, and the importance of their interpretation is becoming more significant. Herein, we present the radiological findings of a variety of complications that can occur after spinal surgery and discuss how effectively and accurately they can be diagnosed through imaging. In particular, this study details the characteristic imaging findings specific to the early and long-term postoperative periods. Early complications of spinal surgery include improper placement of surgical instruments (instrument malpositioning), seromas, hematomas, pseudomeningoceles, and infections in the region surrounding the surgical site. Conversely, long-term complications may include osteolysis around surgical instruments, failure of fusion, adjacent segment disease, and the formation of epidural fibrosis or scar tissue. A precise understanding of the imaging assessments related to complications arising after spinal surgery is crucial to ensure timely and accurate diagnosis, which is necessary to achieve effective treatment. 척추 수술의 빈도 증가와 더불어 radiography, CT, MRI 등의 의료 영상 촬영 건수도 증가하고 있으며, 이와 관련된 영상 판독의 중요성이 점점 더 커지고 있다. 본 논문에서는 척추 수술 후 발생 가능한 다양한 합병증을 이해하고, 이를 정확하고 효과적으로 진단하는 영상 검사의 중요 소견에 대해 다루고자 한다. 특히, 수술 후 초기 및 중장기 합병증을 구분하여, 각 시기별 특징적인 영상 소견을 자세히 설명한다. 척추 수술 후 초기 합병증으로는 부적절한 수술 기구 배치(instrument malposition), 장액종(seroma), 혈종(hematoma), 거짓수막류(pseudomeningocele), 수술 주변 감염(infection) 등이 있으며, 중장기 합병증으로는 수술 기구 주변의 골용해(osteolysis), 융합 실패(failure of fusion), 인접 분절 질환(adjacent segment disease), 경막외 섬유화 또는 흉터 조직(epidural fibrosis or scar) 형성 등이 포함된다. 이러한 척수 수술 후 발생하는 합병증 관련 영상 평가에 대한 정확한 이해는 척추 수술 후 합병증을 적시에 정확하게 진단하여 효과적인 환자 치료에 기여할 것이다.